Moralitas dan Kewajiban: Pemikiran Etis Emanuel Kant - Buran, Silverius Felix; Hayon, Bernadus Suban (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Morality and duty are two central concepts in the ethical thought of Emanuel Kant, a German philosopher who was influential in the history of Western philosophy. Within his deontological ethical framework, Kant emphasized the importance of moral action based on rational and universal principles. He argued that morality does not depend on the consequences of actions, but on the intention and obligation to obey the generally applicable moral law. In his work